Comparative Study of Apperciple Lectures of University Students in The Czech Republic and Slovakia During the First Wave of the COVID-19 Pandemic - Slavomír LACA; Pawel CZARNECKI (Communications of International Proceedings, 2022)
The research study is focused on the perception of online lectures among students in the Czech and Slovak Republics during the first wave of the COVID-19 pandemic within the humanities. The aim of the study: The main goal of the research study was to find out the opinions of students from the Czech and Slovak Republics and subsequently to compare their opinions on online lectures during the first wave of the COVID-19 coronavirus pandemic. Research sample and setup: The research sample of the study consisted of 100 university students of the second degree of humanities, who had (distance) education implemented online (MS TEAMS, ZOOM, etc.) in the first wave of the COVID-19 coronavirus pandemic. All students were informed about the purposefulness of the research study and the completion of the online questionnaire. Statistical analysis:  The mathematical-statistical method chi-square test of the independence of the criteria of individual research hypotheses was used to compare the interviewed university students - respondents in the Czech Republic and Slovakia. Study results: The second-level university students from the humanities at the time of the first wave of the COVID-19 coronavirus pandemic were satisfied with the distance education, as evidenced by the research study and their answers within the questionnaire survey.  From the results of the research survey, it is clear that the participants perceived positively, therefore, apercipled the distance form of education during the first wave of COVID -19.
Keywords: COVID 19; Distance Education; Epidemic; Student.